Understanding static, dynamic and cooperative porosity in molecular materials - Holden,D; Chong,SY; Chen,L; Jelfs,KE; Hasell,T; Cooper,AI (Chemical Science, 2016)
The practical adsorption properties of molecular porous solids can be dominated by dynamic flexibility but these effects are still poorly understood. Here, we combine molecular simulations and experiments to rationalize the adsorption behavior of a flexible porous organic cage.